2012
DOI: 10.1007/s00441-012-1368-x
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane collagen XVII is a novel component of the glomerular filtration barrier

Abstract: The kidney filtration barrier consists of the capillary endothelium, the glomerular basement membrane and the slit diaphragm localized between foot processes of neighbouring podocytes. We report that collagen XVII, a transmembrane molecule known to be required for epithelial adhesion, is expressed in podocytes of normal human and mouse kidneys and in endothelial cells of the glomerular filtration barrier. Immunoelectron microscopy has revealed that collagen XVII is localized in foot processes of podocytes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 32 publications
1
29
0
1
Order By: Relevance
“…There is a recent report showing that the collagen XVII is a component of the podocyte filtration barrier in the kidney glomerular basement membrane [60]. A possible involvement of this transmembrane collagen in the embryonic blood-CSF barrier remains to be studied).…”
Section: Resultsmentioning
confidence: 98%
“…There is a recent report showing that the collagen XVII is a component of the podocyte filtration barrier in the kidney glomerular basement membrane [60]. A possible involvement of this transmembrane collagen in the embryonic blood-CSF barrier remains to be studied).…”
Section: Resultsmentioning
confidence: 98%
“…Human diseases and mouse models have demonstrated that loss of ColXVII expression is associated with rudimentary poorly developed HDs and separation of the epidermis from the basement membrane upon mechanical friction [12], [18], [19]. Here we assessed the adhesive strength of murine Col17a1 − / − keratinocytes using two different in vitro detachment assays.…”
Section: Resultsmentioning
confidence: 99%
“…The generation of the Col17a1 − / − mice has been described elsewhere [12]. Briefly, the targeting vector contained 6.7 kb genomic DNA with arms of 4.3 kb and 2.4 kb.…”
Section: Methodsmentioning
confidence: 99%
“…2). Immunoelectron microscopy has revealed that collagen XVII is localized in foot processes of podocytes and in the glomerular BM (Hurskainen et al 2012). Collagen XVII exists as a full-length transmembrane protein and a soluble 120-kDa ectodomain that is proteolytically released from the cell surface by the sheddases of a disintegrin and metalloproteinase (ADAM) family, ADAM-10, −9 and −17 (Franzke et al 2009).…”
Section: Localized and Intermediate Subtypes Of Junctional Ebmentioning
confidence: 99%
“…Animal models Col17-knockout mice demonstrate skin blisters and display postnatal foot process effacement and glomerular BM splitting (Nishie et al 2007;Hurskainen et al 2012). Nevertheless, no functional studies with regard to glomerular filtration are available and no renal anomalies have been detected in patients with junctional EB lacking collagen XVII.…”
Section: Localized and Intermediate Subtypes Of Junctional Ebmentioning
confidence: 99%